Human T Cell Differentiation Negatively Regulates Telomerase Expression Resulting in Reduced Activation-Induced Proliferation and Survival - Patrick, Michael S.; Cheng, Nai-Lin; Kim, Jaekwan; An, Jie; Dong, Fangyuan; Yang, Qian; Zou, Iris; Weng, Nan-ping (Frontiers in immunology, 2019)
Maintenance of telomeres is essential for preserving T cell proliferative responses yet the precise role of telomerase in human T cell differentiation, function, and aging is not fully understood. Here we analyzed human telomerase reverse transcriptase (hTERT) expression and telomerase activity in six T cell subsets from 111 human adults and found that levels of hTERT mRNA and telomerase activity had an ordered decrease from naïve (T ) to central memory (T ) to effector memory (T ) cells and were higher in CD4 than their corresponding CD8 subsets. This differentiation-related reduction of hTERT mRNA and telomerase activity was preserved after activation. Furthermore, the levels of hTERT mRNA and telomerase activity were positively correlated with the degree of activation-induced proliferation and survival of T cells . Partial knockdown of hTERT by an anti-sense oligo in naïve CD4 cells led to a modest but significant reduction of cell proliferation. Finally, we found that activation-induced levels of telomerase activity in CD4 T and T cells were significantly lower in old than in young subjects. These findings reveal that hTERT/telomerase expression progressively declines during T cell differentiation and age-associated reduction of activation-induced expression of hTERT/telomerase mainly affects naïve CD4 T cells and suggest that enhancing telomerase activity could be a strategy to improve T cell function in the elderly.